THE TURN IN JAPANESE-RUSSIAN RELATIONS IN 2022: CAUSES AND EFFECTS (Південний архів (історичні науки), 2023)
Purpose – indication of the factors, which had an impact on the significant deterioration of Japanese-Russian relations in 2022, as well as the effects of this change. Research methods. In this study the historically-genetic method was used to analyze the historical roots and the direction of changes, that had impacted the nature of Japanese-Russian relations till 2022. The comparative method was utilized to research foreign policy interests and priorities of both Russia and China. Research results. The study analyzes such factors as the unresolved issues of the postwar peace and the territorial status of the Northern Territories (South Kuril Islands), Russian-Chinese rapprochement during the last decade and the Russian-Ukrainian war as well. The consequences of deterioration of Russian-Japanese bilateral relations are examined. Conclusions. Several factors contributed to the deterioration of Japanese-Russian relations. The first factor is the unresolved issue of peace between the two countries after World War II, and also the case of territorial status of the Northern Territories. These issues could not be settled during the Cold War, and the Japanese side repeatedly attempted to reach a common solution with the Russian Federation after the collapse of the Soviet Union. During the second premiership of Sh. Abe, Japanese efforts in this direction were particularly active: it was also necessary to prevent significant rapprochement between Russia and China. This, against the backdrop of the Chinese ambitions could potentially threaten Japan’s safety and national interests. In turn, significant to Russia regarding the division of the Northern Territories, the program of extending bilateral economic cooperation were not succeed. The second factor is the Russian-Chinese rapprochement, which Japan was unable to prevent despite its reconciliation policy towards the Russian Federation. Despite some competition and differences in foreign policy interests, China and Russia share common interests in economic and defensive cooperation, a desire to increase their international status and reduce American global influence. The third factor is the Russian full-scale invasion of Ukraine on February 24, 2022, which was a blatant violation of international law towards an independent and sovereign country by Russia and was accompanied by numerous war crimes. Overall, these factors have considerably worsened Japanese-Russian relations. Japan actively joined the other G7 and EU countries in implementing sanction policy against the Russian Federation, and also began providing significant economic and humanitarian aid to Ukraine while supporting it on an international level. In response, Japan faced unfriendly decisions and actions from the Russian Federation. Given the international context, Japanese- Russian relations are unlikely to be reconciled in the near future.
Keywords: Indo-Pacific, China, international law, the Russian Federation, the Russian full-scale invasion of Ukraine, the Northern territories, Japan